ANALYSIS OF LEGISLATIVE ACTS AND REGULATORY-LEGAL DOCUMENTS REGARDING THE DEVELOPMENT OF LEGAL COMPETENCE OF VOCATIONAL TRAINING TEACHERS AT VOCATIONAL EDUCATIONAL INSTITUTIONS OF CONSTRUCTION INDUSTRY (Innovative professional education, 2024)
Among the priorities of strategies, concepts and programs of the post-war reconstruction of Ukraine, a significant role is assigned to the construction industry. It is important to provide high-quality training of students of professional (vocational and technical) educational institutions in due time. Development of legal competence of vocational training teachers in vocational educational institutions of construction industry is being updated to ensure their ability to form students’ legal competence with their compliance with the issues of regulation of relations in construction market for future dynamics of construction development in Ukraine.
Keywords: vocational education, vocational education teacher, legal competence